2010
DOI: 10.1371/journal.pone.0013430
|View full text |Cite
|
Sign up to set email alerts
|

Bioreducible Liposomes for Gene Delivery: From the Formulation to the Mechanism of Action

Abstract: BackgroundA promising strategy to create stimuli-responsive gene delivery systems is to exploit the redox gradient between the oxidizing extracellular milieu and the reducing cytoplasm in order to disassemble DNA/cationic lipid complexes (lipoplexes). On these premises, we previously described the synthesis of SS14 redox-sensitive gemini surfactant for gene delivery. Although others have attributed the beneficial effects of intracellular reducing environment to reduced glutathione (GSH), these observations can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 61 publications
2
58
0
Order By: Relevance
“…Complexes with positive charges on the particle surface interacted electrostatically with the cell membrane and led to high gene expression. 22) Gene expression was increased with an increase in the protamine charge ratio, and the highest level was observed at charge ratios of 12.8 and 16 (Fig. 2).…”
Section: Discussionmentioning
confidence: 92%
“…Complexes with positive charges on the particle surface interacted electrostatically with the cell membrane and led to high gene expression. 22) Gene expression was increased with an increase in the protamine charge ratio, and the highest level was observed at charge ratios of 12.8 and 16 (Fig. 2).…”
Section: Discussionmentioning
confidence: 92%
“…6,7,11,14 It has been reported that many carriers can augment the efficiency of introducing drugs or nucleotides into glioma cells. 20,[26][27][28][29] One peptide, called VTW, which can selectively bind to GBM cells, indicates another promising approach. 22 One report showed that the VTW peptide specifically increased the uptake of nitric oxide by GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cationic groups commonly used are ammonium [53,54], imidazolium [55][56][57], pyridinium [58,59], lysine or arginine [60][61][62], and/or amine/polyamines [63][64][65][66][67].…”
Section: Cationic Lipids Forming Lipoplexesmentioning
confidence: 99%
“…The electrostatic interaction in lipoplexes formed between GCLs and DNA or RNA, in the presence of a helper lipid as DOPE, DOPC, DMPC and others, have been fully investigated recently. Thus, several groups have studied lipoplexes containing the GCL series formed by two alkyl hydrophobic chains, two ammonium headgroups and an alkyl spacer between them and either DNA [54,66,71,91,[109][110][111][112][113] or siRNA [114]. Other groups have reported the electrostatic interaction when the GCL contains an oligo-oxyethylene spacer [93,115], and/or other headgroups as imidazolium or pyridinium [45, 57-59, 75, 99, 116].…”
Section: Electrostatic Interactionmentioning
confidence: 99%